Teachers’ Strategies in Establishing Positive Relationships to Enhance Students’ Learning Motivation - Sari Chayanti; Mahmud MY (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
Learning motivation in Islamic Religious Education is not only influenced by instructional models but also by the quality of teacher–student relationships. However, existing studies in madrasah contexts tend to emphasize quantitative measurement of motivation rather than examining the relational processes underlying its formation. This study aims to analyze teachers’ efforts in building positive relationships and their implications for students’ learning motivation at MTs Negeri 1 Tanjung Jabung Timur. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. The data were analyzed thematically using an interactive model of data reduction, display, and conclusion drawing. The findings indicate that positive relationships are developed through empathetic attitudes, two-way communication, personal approaches, constructive responses to mistakes, and motivational reinforcement. These practices are strengthened by the madrasah ecosystem, including the 5S culture, collective prayer, and leadership support. The study demonstrates that learning motivation functions as a relational construct shaped by supportive pedagogical interactions that fulfill students’ need for relatedness, resulting in psychological comfort, increased self-confidence, active engagement, and learning persistence. The novelty of this research lies in proposing a relational model of learning motivation that integrates pedagogical practices and institutional culture within the framework of Self-Determination Theory. It concludes that teachers’ relational competence plays a strategic role in fostering intrinsic motivation in madrasah education.